Slovenska dramatika v bolgarskem prevodu. Kako staro postane novo ali kakšni so kriteriji sodobnosti? - Dimitrov, Ljudmil (Amfiteater (Ljubljana), 2022)
The paper focuses primarily on the reception of Slovenian (contemporary) drama in Bulgaria. More precisely, on how texts that fall into a foreign linguistic and sociocultural context, regardless of when they were written, turn out to be new in the host culture and are interpreted according to the problems of our time. The author mainly presents the new collection of five Slovenian plays that he selected and translated. These plays fall within the aesthetic framework of the modern (from modern to postmodernism) and are united by the motif of the miracle, the fantastic, the unnatural (the supernatural). The motivation for his choice is twofold. After the (un)expected great success of the first collection, Lurking for Godot. Five Contemporary Slovenian Plays (2014), three of which were staged on the Bulgarian stage (one of them three times), the second collection tries not just to meet the Bulgarian audience and Bulgarian theatre with Slovenian classics but to include itself in Bulgaria's own dramatic tradition, in which the dominant motif is the myth, the miracle, the infernal. Can we make sense of the other through our own? How new is the old?
Keywords: bolgarski jezik; prevodi; recepcija; slovenska dramatika